Penerapan Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah (SAK-EMKM) Pada UMKM Pentol Kabul - Naila Syifa Azahra; Nensi Rahma Nor Hakiki; Citra Helena Rahmawati; Olivia Lovina Hermanto; Trifena Hanayomi Sutanto; Sri Rahayuningsih (Pusat Riset dan Inovasi Nasional, 2024)
SAK EMKM is expected to assist entities in transitioning from cash-based financial reporting to accrual-based financial reporting. The issuance of SAK EMKM is expected to serve as one of the drivers of financial literacy for MSMEs in Indonesia, thus widening their access to financing from the banking industry. Financial statements are records of financial information of a company during an accounting period that explain a company's performance. The purpose of financial statements according to PSAK 1 (Revised 2009) is to provide information about the financial position, financial performance, and cash flows of an entity to assist most users of the financial statements in making economic decisions. SAK-EMKM contains simpler accounting regulations than SAK-ETAP because MSMEs conduct transactions with calculations and measurements that purely use historical costs. The type of research method used is descriptive qualitative method. Describing the current financial condition of MSME players. As well as conducting a simple financial statement preparation analysis for MSME players. This study produces financial statements for Pentol Kabul MSMEs that comply with SAK-EMKM standards, including balance sheets, income statements, and notes to the financial statements.